Natural chromenes and chromene derivatives as potential anti-trypanosomal agents - Batista Jr., João Marcos [UNESP]; Lopes, Adriana Aparecida [UNESP]; Ambrósio, Daniela Luz [UNESP]; Regasini, Luis Octávio [UNESP]; Kato, Massuo Jorge; Bolzani, Vanderlan da Silva [UNESP]; Cicarelli, Regina Maria Barreto [UNESP]; Furlan, Maysa [UNESP] (Pharmaceutical Society of Japan, 2008)
The aim of the study was to investigate the anti-trypanocidal activities of natural chromene and chromene derivatives. Five chromenes were isolated from Piper gaudichaudianum and P. aduncum, and a further seven derivatives were prepared using standard reduction, methylation and acetylation procedures. These compounds were assayed in vitro against epimastigote forms of Trypanosoma cruzi, the causative agent of Chagas disease. The results showed that the most of the compounds, especially those possessing electron-donating groups as substituents on the aromatic ring, showed potent trypanocidal activity. The most active compound, [(2S)-methyl-2-methyl-8-(3″-methylbut-2″-enyl)-2- (4′-methylpent-3′-enyl)-2H-chromene-6-carboxylate], was almost four times more potent than benznidazole (the positive control) and showed an IC 50 of 2.82 μM. The results reveal that chromenes exhibit significant anti-trypanocidal activities and indicate that this class of natural product should be considered further in the development of new and more potent drugs for use in the treatment of Chagas disease. © 2008 Pharmaceutical Society of Japan.
Keywords: Chromene; Piper aduncum; Piper gaudichaudianum; Piperaceae; Trypanosoma cruzi; antitrypanosomal agent; benznidazole; chromene derivative; methyl 2 methyl 8 (3'' methylbut 2'' enyl) 2 (4' methylpent 3' enyl)2h chromene 6 carboxylic acid; unclassified drug; acetylation; Chagas disease; controlled study; drug activity; drug isolation; drug potency; electron; IC 50; in vitro study; methylation; nonhuman; Animals; Benzopyrans; Parasitic Sensitivity Tests; Piper; Structure-Activity Relationship; Trypanocidal Agents